The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1017/s0959269510000499
|View full text |Cite
|
Sign up to set email alerts
|

Permanence et variation des unités prosodiques dans le discours et l'interaction

Abstract: RÉSUMÉNotre objectif est de montrer que les unités définies en laboratoire par la phonologie intonative sont non pas seulement identifiables dans la « parole naturelle », mais-jouent également un rôle discursif et interactionnel. Cependant, en vue de procéder à leur identification, on doit réussir à séparer, dans des données non contrôlées, la structure phonologique des autres types d'information encodés par la prosodie. Cela inclut à la fois des variations prosodiques « orthogonales » et graduelles de registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…To identify a period boundary all the following conditions must be present: a pause of at least 300 ms, significant F0 movement, and pitch reset. Portes & Bertrand (2011) argued for a phonological structuration of spontaneous speech into several phrasing levels like those of read speech. They suggested that this structuration is only affected by disfluencies and interactional processes such as turn-taking and backchannels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify a period boundary all the following conditions must be present: a pause of at least 300 ms, significant F0 movement, and pitch reset. Portes & Bertrand (2011) argued for a phonological structuration of spontaneous speech into several phrasing levels like those of read speech. They suggested that this structuration is only affected by disfluencies and interactional processes such as turn-taking and backchannels.…”
Section: Discussionmentioning
confidence: 99%
“…For the French dataset, once primary and secondary stresses have been identified, the main acoustic cues are (1) specific melodic contour, (2) final lengthening, (3) pitch reset. Disfluencies were annotated separately and silent pauses have not been systematically associated with a boundary (Portes et al 2011). …”
Section: The French Datamentioning
confidence: 99%
“… AC-IP, which corresponds to the last metrical syllable of any IP, IP boundaries being located at the end of a clause, a detached syntactic constituent, or a line (in poems and rhymes), see [14], [17] and [18] among others.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, accented syllables, which correspond to the last full syllable at any level of prosodic structure, are lengthened, the lengthening rate being generally related to the level of phrasing (e.g. [15], [18]). Lengthening rates were thus computed by comparing the duration of vowels in unaccented syllables with the duration of the nucleus of any last metrical syllables (i.e.…”
Section: Prosodic Structure and Duration Patternsmentioning
confidence: 99%
“…Dans les approches guidées par la réalisation physique des phénomènes prosodiques (Jun & Fougeron, 2002), le SI est défini comme un groupe prosodique comprenant minimalement un GA, lequel est assorti d'un accent nucléaire. En français, les accents nucléaires sont marqués par un mouvement mélodique majeur, montant, descendant ou montantdescendant (Portes, 2004), un allongement relatif et la présence d'une pause après (D'Imperio et al, 2007;Portes & Bertrand, 2011). Ils présentent la particularité d'être "contourogènes", c'est-à-dire de générer "une configuration mélodique identifiable (perceptivement et linguistiquement) comme un contour" (Di Cristo, 2010).…”
Section: Dans Les Approches Guidéesunclassified